Administrative Boundaries and Legal Control over Integrity Commission Decisions in Iraq - Kazim, Noor Ali (Indonesian Journal of Law and Economics Review, 2025)
General Background: After 2003, Iraq witnessed a major transformation in its administrative and legal systems, marked by the establishment of independent bodies to fight corruption, most notably the Federal Integrity Commission. Specific Background: Despite extensive legislative reforms, persistent ambiguity remains regarding the boundaries between administrative authority and the Commission’s jurisdiction, raising questions about the implementation and legitimacy of integrity decisions within the framework of Iraqi law. Knowledge Gap: Previous studies have not comprehensively analyzed the legal limits of administrative power vis-à-vis the Integrity Commission’s decisions or the judicial interpretations that define these boundaries. Aims: This study aims to examine the extent of administrative compliance with the Integrity Commission’s decisions, clarify the constitutional and legislative foundations governing their relationship, and analyze judicial oversight in this context. Results: The research reveals that while the Integrity Commission possesses significant investigative authority, the administration retains limited discretion under strict judicial and legal constraints to ensure the rule of law. Novelty: By integrating legislative analysis with constitutional jurisprudence, the study offers a nuanced framework explaining how executive power interacts with independent anti-corruption mechanisms. Implications: The findings underscore the necessity for clearer constitutional delineation and stronger judicial safeguards to preserve institutional integrity and ensure balanced governance in Iraq. Highlights: Defines clear legal boundaries between administrative powers and the Integrity Commission’s authority. Highlights the judiciary’s central role in ensuring balance and legality in anti-corruption actions. Emphasizes the need for constitutional clarity and stronger institutional independence. Keywords: Integrity Commission, Administrative Authority, Iraqi Legislation, Judicial Oversight, Anti-Corruption